Terminologiebestuur binne die Suid-Afrikaanse konteks - Goosen, Michelle; Taljard, Elsabé (Lexikos, 2025)
Terminology Management in the South African Context. This article examines the systematic management of terminological information in South Africa through the use of terminology management systems. It argues for a structured approach to terminology management across different contexts, namely at macro, meso, and micro level. The focus is specifically on terminology management within the commercial context, where it can enhance productivity within an organisation, ensure effective communication, and improve return on investment. The importance of user-oriented terminological products is emphasised, with specific attention given to the profile of the target user. Various types of software for terminology management, namely standalone, internet-based, and mobile applications, are discussed. This discussion also includes the knowledge-based approach to terminology. The article proposes a practical terminology workflow diagram suited to the multilingual South African context. It highlights the necessity of further research, institutional support, and user involvement to establish a sustainable terminology infrastructure in South Africa.Keywords: terminology management, terminology management systems, terminology products, commercial context, return on investment, macro, meso and micro level, target user, software, knowledge-based approach to terminology, terminology workflow diagram